Exploring the potential duty of care in clinical genomics under UK law. (September 2017) - Mitchell, Colin; Ploem, Corrette; Chico, Victoria; Ormondroyd, Elizabeth; Hall, Alison; Wallace, Susan; Fay, Michael; Goodwin, Deirdre; Bell, Jessica; Phillips, Simon; Taylor, Jenny C.; Hennekam, Raoul; et al.
Genome-wide sequencing technologies are beginning to be used in projects that have both clinical diagnostic and research components. The clinical application of this technology, which generates a huge amount of information of varying diagnostic certainty, involves addressing a number of challenges to establish appropriate standards. In this article, we explore the way that UK law may respond to three of these key challenges and could establish new legal duties in relation to feedback of findings that are unrelated to the presenting condition (secondary, additional or incidental findings); duties towards genetic relatives as well as the patient and duties on the part of researchers and professionals who do not have direct contact with patients. When considering these issues, the courts will take account of European and international comparisons, developing guidance and relevant ethical, social and policy factors. The UK courts will also be strongly influenced by precedent set in case law.